Opportunities for and Challenges of Conducting Indirect Treatment Comparisons and Meta-Analyses for Vaccines in Post-EU HTA Regulation Era - Charlotte Graham; Erin Barker; Joe Moss; Emily Gregg; Rachael McCool; Nathalie Largeron; Mélanie Trichard; José Bartelt-Hofer; Maribel Tribaldos (Journal of Market Access & Health Policy, 2025)
The dynamic nature of infectious diseases introduces inherent challenges to the design of vaccine clinical trials, which consequently makes vaccine indirect treatment comparisons (ITCs) and meta-analyses (MAs) more challenging compared with regular pharmaceuticals. However, comparisons of efficacy and safety between vaccines are being frequently required in vaccine decision making due to a low number of head-to-head clinical trials in the vaccine landscape. The introduction of the European Union Health Technology Assessment (HTA) Regulation (EU HTAR) aims to harmonize HTA efforts across Europe. However, the EU HTAR could also escalate existing challenges for conducting vaccine MAs and ITCs. Such challenges include generating efficacy evidence in time for Joint Clinical Assessment (JCA), incorporating high levels of heterogeneity due to infectious disease-specific characteristics, and tackling a high number of PICOs per submission—likely driven by heterogeneity in the available data and differences in national vaccine calendars. Opportunities to tackle these challenges include introducing a stepwise approach to vaccine assessment in JCA, best-practice recommendations for conducting/interpreting vaccine MAs and ITCs, and condensing the number of PICOs to create larger ‘catch-all’ ITC networks. This perspective article explores these challenges and opportunities further.